Sustainability of Darangan Water Service Development Cooperative: Basis for Strategic Plan - Balaga, Lourd Jeremiah (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the sustainability of the Darangan Water Service Development Cooperative (DWSDC) as the basis for developing a strategic plan for 2026–2030. Specifically, it examined the cooperative's financial performance, operational resilience, and community engagement through key sustainability indicators, including net surplus, earnings per share (EPS), return on equity (ROE), revenue growth, and surplus allocation. A descriptive research design utilizing documentary analysis was employed, with audited financial statements from 2022–2024 serving as the primary data source. Benchmarking was also conducted against selected neighboring cooperatives in Binangonan, Rizal to evaluate comparative financial performance and operational practices. Findings revealed that DWSDC demonstrated consistent financial growth, generating ₱18.67 million in gross revenues and a net surplus of ₱3.25 million in 2024, supported by increasing members' equity and prudent allocation of statutory reserves. However, rising administrative costs and dependence on water operations highlight the need for enhanced cost efficiency, service diversification, and risk management. The study concludes that a structured strategic planning framework is essential to sustain financial stability, strengthen organizational resilience, improve operational efficiency, and enhance community trust. Accordingly, a five-year strategic plan emphasizing resource optimization, infrastructure development, technological innovation, climate resilience, capacity building, and external resource mobilization is recommended to ensure the cooperative's long-term sustainability and competitiveness.
Keywords: Sustainability, Strategic Planning, Water Service Cooperative, Financial Performance, Operational Resilience, Cooperative Management, Benchmarking, Darangan Water Service Development Cooperative.